There’s no hope : The global economic crisis and the politics of resistance in Southern Europe - Ugo Rossi (Belgeo)
Since 2010 Southern Europe has become the epicentre of the second phase of the global economic crisis that began two years earlier as a consequence of the bursting of the mortgage and financial bubble in the United States. In critical commentaries, this crisis has been understood as a crisis of neoliberalism as a mode of economic-political regulation. In the first part, this paper analyses the transition to a neoliberal mode of economic governance in Italy, understood in terms of “concerted neoliberalism”, particularly looking at its implications for the North-South divide. In the second part, the paper looks at the effects of the global crisis in the Sardinia region, through the lens of the politics of resistance that has taken shape in this context. The paper concludes by reflecting on the limits to a regionalised politics of resistance, calling for an imaginative politics of renaissance at a cross-Southern European scale.